2020
DOI: 10.1002/ejp.1551
|View full text |Cite
|
Sign up to set email alerts
|

Association between objectively measured physical behaviour and neck‐ and/or low back pain: A systematic review

Abstract: Background and objective Clinical guidelines recommend physical activity to manage neck pain (NP) and low back pain (LBP). However, studies used to support these guidelines are based on self‐reports of physical behaviour, which are prone to bias and misclassification. This systematic review aimed to investigate associations between objectively measured physical behaviour and the risk or prognosis of NP and/or LBP. Databases and data treatment Literature searches were performed in MEDLINE, Embase and Scopus fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 91 publications
3
28
2
Order By: Relevance
“…Thus, sitting may be needed to allow rest and recovery, and prevent aggravated symptoms that contribute to sick-leave spells [38]. This would corroborate previous prospective studies using device-worn measurements indicating a negative association between sitting time and MSP in blue-collar workers [12]. To account for the possibility of this association merely occurring because of sitting being inversely related to physical activity, we adjusted for relative time spent in standing, LIPA, and MVPA, along with other relevant covariates.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Thus, sitting may be needed to allow rest and recovery, and prevent aggravated symptoms that contribute to sick-leave spells [38]. This would corroborate previous prospective studies using device-worn measurements indicating a negative association between sitting time and MSP in blue-collar workers [12]. To account for the possibility of this association merely occurring because of sitting being inversely related to physical activity, we adjusted for relative time spent in standing, LIPA, and MVPA, along with other relevant covariates.…”
Section: Discussionsupporting
confidence: 82%
“…Sick leave due to MSP is of multifactorial origin and a variety of possible occupational determinants of future sick leave due to MSP have been identified-for example, high physical work demands and poor psychosocial working conditions [4][5][6][7][8][9]. Time spent in daily physical behaviors such as sitting, standing, and physical activity has profound physiological and psychological effects that may extend to the onset and progression of MSP [10][11][12] and the ability to remain at work [13][14][15][16]. Overall, very few studies have addressed physical behaviors at work in relation to sick leave specifically due to MSP [17].…”
Section: Introductionmentioning
confidence: 99%
“…It is clinically more intuitive that better physical function is related to better prognosis, given that enhanced function is the aim of many therapeutic efforts. In the wider musculoskeletal literature, there have been reports of paradoxical relationships between physical function and pain, such as: (1) greater spine mobility predicting poorer recovery in back pain 38 , (2) greater physical activity levels increasing the risk of spinal pain onset 39 , and (3) greater hip internal rotation mobility, as one factor, increasing the responsiveness to manual therapy in back pain 40 . The predictors selected in the present study should not be interpreted causally but be restricted to the predictive framework.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a recent systematic review found increased sitting time at work to associate with less intense LBP among physical workers. 39 Besides, hard physical work during early life is bringing workers closer to a musculoskeletal pain threshold that is associated with an increased risk of sickness absence due to LBP. Andersen and coworkers found female eldercare workers to be at elevated risk of sickness absence due to LBP when their pain intensity was 5.0 on the 0-9 NRS.…”
Section: Interpretation Of Findingsmentioning
confidence: 99%